AL-THÛFÎ : REPRESENTASI KAUM LIBERALIS TERHADAP PEMBENTUKAN HUKUM ISLAM - Mufid, Moh (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2016)
The dynamics of Islamic legal thought continue rolling relentlessly. One of the frequently asked questions discourse in academic circles is about the concept of affairs. The most controversial are considered related that concept was Najm al-Din al-Thûfî. In his work, al-Thûfî seek elaborating the thought of his predecessors. The thought of al-Thûfî that's cause he is regarded as a liberal figure, for daring to